SURVEY OF PARASITES OF Synodontis schall IN DADIN KOWA DAM, GOMBE STATE, NIGERIA - Garkuwa, Nuru A.; Rueben, Bilikisu; Isah, Zainab; Aliyu, Sani Ibrahim; Abubakar, Bara‘atu; Umar, Zaliha Adamu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Parasitic disease of fish seems to be one of the major problems confronting fish culturists. A parasitic infestation leads to serious consequences especially to the nutritive devaluation of the fish. Therefore the Endoparasites and Ectoparasites of Synodontis schall (up-side down catfish) from Dadin Kowa dam were investigated. In this research, there was no ectoparasite found in this research. Out of the 50 specimen examined, there was no ectoparasite. However, 27 were found to be infected by three species of endoparasites viz: Eustrongylides sp, Procallamus sp and Diphyllobothrium latum were recovered from the stomach and intestine of the sampled fish species. A total of 90 helminthes were identified from Synodontis schall; Nematodes accounted for (83.34%) and Cestode (16.67%). There was no significant difference (p>0.05) in the parasite load between the male and female species when examined statistically. The females of the fish species had higher parasitic prevalence (34.0%) than the males (20.0%) suggests that females may be more prone to infection during breeding periods. It was also observed that the intestine of the sampled fish had higher percentage parasite load suggesting that fish diet in the fishing ground were responsible for high rate of infestation of Synodontis schall. Therefore, it is recommended that there is need for proper cooking of fish before consumption.